5(v-2)=-2(7-3v)-4

Simple and best practice solution for 5(v-2)=-2(7-3v)-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(v-2)=-2(7-3v)-4 equation:



5(v-2)=-2(7-3v)-4
We move all terms to the left:
5(v-2)-(-2(7-3v)-4)=0
We add all the numbers together, and all the variables
5(v-2)-(-2(-3v+7)-4)=0
We multiply parentheses
5v-(-2(-3v+7)-4)-10=0
We calculate terms in parentheses: -(-2(-3v+7)-4), so:
-2(-3v+7)-4
We multiply parentheses
6v-14-4
We add all the numbers together, and all the variables
6v-18
Back to the equation:
-(6v-18)
We get rid of parentheses
5v-6v+18-10=0
We add all the numbers together, and all the variables
-1v+8=0
We move all terms containing v to the left, all other terms to the right
-v=-8
v=-8/-1
v=+8

See similar equations:

| 129=2x+5(2x–3) | | 406.92=180+.93x | | m/2-13=-8 | | 23x–1=32 | | -3x-9=2x-8 | | |-8p|+4=20 | | 14=10+b/4 | | 35=5x+13+6x | | 3n+46=12n+10 | | x−15=−41 | | d-91÷4=2 | | x/14=14/21 | | 21=6-5/8k | | 7w-35=2w+85=180 | | 4x-25=130-2x-1 | | d−91^4=2 | | -3(-2k-4)-3k=5(k+4) | | 300=-16^2x=175x+1 | | 4/5w-6=6 | | 3(4x-7)2(4x-7)=5 | | 5/4(2-k)=2(3k-1)-2/3k | | 90=37.07+.50x | | 6w-15=3w+45=180 | | 12x^2+19x+3=0 | | g2+23)g=6 | | (x3-4x2+4x-1)÷(x=-1) | | 4(5x+1)-9=20x-5 | | x=2837.51-0.054203x | | 2b+9)b=3 | | 4w+10=2w+60=180 | | 90+(2x-3)=(10x-17) | | s^2+2-6=0 |

Equations solver categories